The Development of Malaysian University Choir: Current Choral Practices from the Perspectives of Choir Members and Conductors - DAYANG SITI AISHAH, AWANG MATALI (Universiti Malaysia Sarawak (UNIMAS), 2018)
The purpose of this study was to study the development of Malaysian university choirs. This study focused specifically on the three elements of university choir experiences, problems and challenges faced by university choir members and conductors, and initiatives undertaken by choir members and conductors to improve the quality of choir singing. Although the number of university choirs has multiplied over the past twenty years due to the increased tertiary music programmes being offered in Malaysia, very few studies have been conducted from the perspective of choir members and choral conductors. In seeking greater understanding in this area, this study was conducted via quantitative and qualitative methods. A questionnaire was distributed to choir members and interview sessions were conducted with three choral conductors from selected universities to gain insight into their experiences with the choirs, to discuss the challenges they faced, and to seek strategies in improving the overall quality of the choir. Result of the study show that all choir members and choral conductors consider choral activities to be important. They also share their ideas and suggestions on means to improve the quality of choirs singing in Malaysian universities. The findings indicate financial constraint to be the biggest challenge faced by both the choir groups as well as the choral conductors. Besides, greater opportunities to get involved in performances and competitions especially outside Malaysia was an essential contributor to ensure a better standard of the choir as a whole. It was evident that a lot of talents are supposed to be seen and assisted as they are also contributing to the good reputation of the university as well as the country. Financial problem should not be an obstacle to the development of choir in Malaysia. Therefore, this study provides a better understanding of the development of university choirs in Malaysia by looking at the choir members’ and choral conductors’ experiences, identifying challenges, and formulate possible strategies in order to raise the overall standard of university choirs in Malaysia.